Validity, reliability and psychometric properties of the Italian version of the Nurses’ Cancer Pain Management Competency Scale - Damico, Vincenzo; Pedrini, Manuela; Demoro, Giuseppe; Cossalter, Luca; Murano, Liana; D’Alessandro, Antonella; Fermi, Lara; Milani, Margherita; Russello, Giuseppe; Margosio, Viola (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background and aim. The Nurses’ Cancer Pain Management Competency Scale (NCPMCS) is a tool developed to assess nurses’ competencies and subjective experiences in cancer pain management. It also supports awareness of their limitations. Assuming cancer pain is not limited to oncology, we evaluated the psychometric properties of the scale among general Italian nurses.Methods. A cross-sectional study enrolled nurses from 16 hospitals across Northern, Central, and Southern Italy. Convenience sampling was used to select nurses who met inclusion criteria. Participants completed the study to validate the Italian version of the NCPMCS. Internal consistency was assessed with Cronbach’s alpha; construct validity with exploratory factor analysis. Data were collected in July 2024.Results. The final sample included 128 nurses, 68% of whom were female. Factor loadings ranged from 0.81 to 0.92, and t-values exceeded 1.96 for all 14 items. On a 4-point scale, the overall competency mean was 1.94 ±0.81. The highest mean score was for the multidimensional nature of pain (2.01 ±0.93); the lowest was for pain management (1.87 ±0.83). Cronbach’s alpha was 0.806 (range 0.719–0.836). Fit indices indicated acceptable model adequacy: χ²/df = 2.662, GFI = 0.854, RMSEA = 0.037, AGFI = 0.876, CFI = 0.928.Conclusion. The Italian version of the NCPMCS is a valid and reliable instrument to assess cancer pain management competencies in nurses, including those outside oncology departments.